Student evaluation procedures: changes from the Bachelor to Degree? - María Luisa García Hernández; Mónica Porto Currás; Nicolás Martínez Valcárcel (Universitat Politècnica de València, 2015)
One of the proposals defended by the European convergence process was a shift in the model of the teaching-learning process which affected the teaching role and the pupil role. Obviously, the put in practice of new teaching ways, new methodologies, should have a reflection in changes of the assessment process so that the evaluation can be adapted to this new idea. In this way, the goal of this article is to go deeper in the evaluation process, more concretely to know in the procedures used to gather information about the learning process of our students and how the way of assessing them has a certain influence in their formation such as oncoming professionals in the field of Pedagogy. For this article, data related to  the  degree in  Pedagogy  (Education School) in the University of Murcia have been  collected.  In  particular,  we  have worked with three different promotions in Pedagogy (two of them from the Bachelor in Pedagogy and another one from the degree in Pedagogy), taking our students experience as a primary source of  information.  From  this  analysis  we can firstly outline that the combination of two or more procedure to gather varied  information  about  the  learning process of the students and secondly, the existing continuity in the use of evaluation procedures in both curriculum, in the evolution from the Bachelor to the Degree in Pedagogy